Consumption of Hibiscus sabdariffa dried calyx ethanol extract improved redox imbalance and glucose plasma in vitamin B12 restriction diet in rats - Irena Ujianti; Sianipar, Imelda Rosalyn; Prijanti, Ani Retno; Santoso, Dewi Irawati Soeria (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to evaluate the effect of Hibiscus sabdariffa L. dried calyx ethanolic (HSE) extract on the redox imbalance and glucose plasma of vitamin B12 restriction Sprague-Dawley rats. The rat was fed a Vitamin B12 Restriction Diet for 16 weeks and treated with HSE as the treatment group. One group was fed a restriction diet not treated with HSE as a positive control group, and another was fed a control chow diet not treated with HSE as a negative control group. Vitamin B12, MDA, SOD activity enzyme, and glucose levels were evaluated in this study. The extract had a significant antioxidant capacity in terms of reducing the production of free radical scavenging activity. The HSE can repair the skewed redox imbalance and oxidative damage generated by a vitamin B12-deficient diet in the rat liver. The result of fasting glucose plasma levels, in 16 weeks showed both significantly different in all groups. In Sprague-Dawley rats with vitamin B12 restriction treated with HSE, a decrease in the glucose plasma in week sixteen was observed, together with a reduction of hepatic redox imbalance. Treatment with HSE protected hepatocytes from oxidative damage caused by vitamin B12 deficiency.